Aspects that facilitate or difficult nurse’s training in primary health care - Montenegro, Livia Cozer; Brito, Maria Jose Menzes (Investigación y Educación en Enfermería, 2011)
Objective. To describe the aspects that facilitate or difficult nurse’s training in primary health care (PHC). Methodology. Qualitative case study carried out in 2009. 15 nurses, who worked in the Family Healthcare Teams of the Basic Health Units of Belo Horizonte, under an agreement with the Nursing school of the Federal University of Minas Gerais through the Reorientation Program of Healthcare Professional’s Training, participated in the study. Subjects were interviewed and data underwent content analysis. Results. The greatest difficulty is continuing PHC training after graduation. The main facilitating aspects were: Studying in a public university, more experienced professional’s escort, a rural internship, and the participation of teachers specialized in public health. Conclusion. Training deficiencies from graduated nurses to work in PHC can be corrected through the application of theory and practice teaching strategies at the universities.